Feasibility Test of Reproductive Health Gymnastics Video Media for Socialization to Adolescent Girls - Widyaning Dara Utami; Rr.Sri Endang Pujiastuti; Mateus Sakundarno Adi (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Reproductive health gymnastics is a type of physical activity which if done regularly can increase hemoglobin level. The development of socialization media in the form of reproductive health gymnastics videos has been carried out, but its feasibility is not yet known. Objective: To test the feasibility of the reproductive health gymnastics video media as a media for socializing reproductive health gymnastics to adolescent girls. Methods: Research and development is limited to the feasibility test of video media with 3 samples of experts and 30 samples of adolescent girls. Results: the intraclass correlation coefficient test obtained a value of ρ value 0.017 <0.05, which means that reproductive health gymnastics videos are relevant and appropriate as a media for socializing reproductive health gymnastics to adolescent girls. Discussion: reproductive health gymnastics videos are relevant and appropriate as a media for socializing reproductive health gymnastics to adolescent girls.